The Relationship Between Family Socioeconomic Status and Feeding Patterns for Toddlers at the Saritani Community Health Center, Boalemo - Sitti Hermawati S. Napu; Rani Safitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Toddlers are a critical age group 0–59 months who require optimal nutritional intake to support physical and cognitive growth and development. The quality of toddler feeding patterns is influenced by family socioeconomic factors, including income, education, and parental occupation. This study aims to analyze the relationship between family socioeconomic status and toddler feeding patterns in the working area of the Saritani Community Health Center, Boalemo Regency. This study used an observational design with a cross-sectional approach and involved 40 respondents selected using purposive sampling. Data were collected through structured questionnaires, interviews, observations, and secondary data from the Community Health Center, then analyzed using the Chi-Square test with a significance level of p < 0.05 . Results: Most families have middle (45%) and low (40%) socioeconomic status. Good feeding patterns are received by 55% of toddlers, while 45% have inadequate feeding patterns. The analysis shows a significant relationship between family socioeconomic status and toddler feeding patterns (p = 0.043). Families with low incomes and limited maternal education tend to provide food with less than optimal variety and nutritional content. Conclusion: Family socioeconomic status has a significant influence on toddler feeding patterns in Saritani.